Mesobuthus eupeus (Scorpiones: Buthidae) from Iran: A polytypic species complex - Mirshamsi, Omid; Sari, Alireza; Elahi, Elahe; Hosseinie, Shidokht (Zootaxa, 2011)
In the present study a number of scorpions from Iran classified under the name of Mesobuthus eupeus (C.L. Koch, 1839) were considered. Currently, M. eupeus includes at least 14 described subspecies with no concrete taxonomic position. Here, this species is redescribed based on new specimens collected from Iran. In addition, multivariate statistical analyses were performed to investigate the degree of intraspecific morphological divergence of M. eupeus based on six Iranian subspecies. The results of morphological comparisons and univariate and multivariate statistical analyses confirm the high phenotypic variability within this species. The data presented here revealed two distinct groups: I. M. e. phillipsi and, II. Including five subspecies namely, M. e. eupeus, M. e. philippovitschi, M. e. thersites M. e. afghanus and M. e. kirmanensis. The results of this study clearly confirm the hypothesis that M. eupeus is a polytypic species complex and possibly includes more than one valid species. Therefore, according to comparative morphological analysis, M. e. phillipsi was raised to the species level.